High School Teachers in Mexico. Their heterogeneity and particularity - Fonseca-Bautista, César Darío (2020)
This paper aims to analyze the heterogeneity and particularity of high school teachers in Mexico. Our perspective is that the heterogeneity of high school subsystems is unevenly distributed. The sample comprised 24 teachers from three high schools belonging to different subsystems and geographical regions. Quantitative and qualitative information was obtained and analyzed from four axes: admission to teaching, teacher’s profile, working and salary conditions, and union participation. The main findings include the identification of three particular school spaces with their own school culture. In one institution, working positions are obtained through a knowledge exam; in another institution, they have exams for public service; in a third one, they consider influences and recommendations from groups of power. In two schools, teachers lead whichever subjects the institution requires, while in only one, they teach the subject for which they presented the exam. The heterogeneity and diversity of teachers need to be noticed by the educational policies considering that they tend to standardize their evaluations, and this reveals the lack of coherence between the educational policy, the diversity of regional, political and cultural contexts and the dynamics of each educational subsystem. In view of such fragmented operational and regulatory, institutional scenario (considering the 40 high school education subsystems), consensus, awareness, and coordination efforts of the federal educational authority are decisive for them to have - without giving up diversity- “communicating vessels” in strategic points of the national educational policy.